2005
DOI: 10.1002/syn.20216
|View full text |Cite
|
Sign up to set email alerts
|

PET imaging of glucose metabolism in a mouse model of temporal lobe epilepsy

Abstract: Here we present the first demonstration that 2-deoxy-2[18F]fluoro-D-glucose (18FDG) and micro Positron Emission Tomography (microPET) can be used successfully to monitor regional changes in brain metabolism during acute seizure induction in C57Bl/6 mice. These longitudinal studies show a significant increase in 18FDG uptake in the hippocampus (33.2%) which correlates directly with seizure severity (R2=0.86). 18FDG microPET can potentially be used to monitor the development of TLE in mouse models from the acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 22 publications
(22 reference statements)
1
52
0
2
Order By: Relevance
“…Small animal imaging using microPET has become an increasingly useful tool in multiple research areas (Schiffer et al, 2005;Schiffer et al, 2006a;Sossi and Ruth, 2005). However, existing image analysis strategies for small animal PET data are targeted toward examining regional changes in 18 FDG uptake, as we have shown for an animal model of TLE (Mirrione et al, 2006). Here we describe a way to use statistical parametric mapping (SPM), an advanced image analysis strategy commonly used in human imaging studies, to develop a high-throughput and clinically relevant method to elucidate brain/behaviour relationships in animal models of human disease.…”
Section: Introductionmentioning
confidence: 99%
“…Small animal imaging using microPET has become an increasingly useful tool in multiple research areas (Schiffer et al, 2005;Schiffer et al, 2006a;Sossi and Ruth, 2005). However, existing image analysis strategies for small animal PET data are targeted toward examining regional changes in 18 FDG uptake, as we have shown for an animal model of TLE (Mirrione et al, 2006). Here we describe a way to use statistical parametric mapping (SPM), an advanced image analysis strategy commonly used in human imaging studies, to develop a high-throughput and clinically relevant method to elucidate brain/behaviour relationships in animal models of human disease.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no report that has described an obvious relationship between dystonia and the hippocampus, although there are many studies that show a relationship between the hippocampus and epilepsy. Thus, Mirrione et al (2006) observed a significant increase in the glucose metabolism in the hippocampus and insignificant hypermetabolism in the thalamus and striatum by PET in a mouse model of epilepsy. These findings would suggest that epileptic seizures are related to abnormal activity of the basal gangliathalamo-cortical motor circuit (Raggenbass and Bertrand 2002;Degos et al 2008).…”
Section: Regional Changes In [ 14 C]dg Uptake During Dystoniamentioning
confidence: 89%
“…ROI analysis was based on the mouse atlas of Mirrione et al (11), with modifications to produce an 11-ROI template consisting of striatum, cortex, hippocampus, thalamus, cerebellum, basal forebrain and septum, hypothalamus, amygdala, caudal brain stem, olfactory bulb, and midbrain, along with a whole-brain ROI equaling the total of all the other ROIs.…”
Section: Pet/ct Imagingmentioning
confidence: 99%
“…The ability to follow single animals or groups of animals using repeated scans should improve accuracy (by potentially reducing the effect of variability between animals) and reduce the number of animals required for studies, with the corollary of a significant lowering of costs when working with transgenic cohorts. However, attempts to measure changes in mouse brain metabolism have met with mixed results: uptake of 18 F-FDG correlated well with 14 C-DG uptake in normoglycemic animals (10), and 18 F-FDG PET has been used to reveal metabolic phenotypes in models of epilepsy (11,12) and Alzheimer disease (13)(14)(15)(16)(17)(18)(19)(20)(21). However, others have failed to detect differences in mouse models of Alzheimer disease (22,23) and the question may be raised of whether phenotypes are due to different acquisition and analysis methods yielding different sensitivities in identifying neuronal alterations.…”
mentioning
confidence: 99%